2013
DOI: 10.4161/epi.26334
|View full text |Cite
|
Sign up to set email alerts
|

The cellular ratio of immune tolerance (immunoCRIT) is a definite marker for aggressiveness of solid tumors and may explain tumor dissemination patterns

Abstract: The adaptive immune system is involved in tumor establishment and aggressiveness. Tumors of the ovaries, an immune-privileged organ, spread via transceolomic routes and rarely to distant organs. This is contrary to tumors of non-immune privileged organs, which often disseminate hematogenously to distant organs. Epigenetics-based immune cell quantification allows direct comparison of the immune status in benign and malignant tissues and in blood. Here, we introduce the "cellular ratio of immune tolerance" (immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…Such a situation was present in [ 29 ]. In their study, a set of three pre-identified gene regions was considered.…”
Section: Resultsmentioning
confidence: 83%
“…Such a situation was present in [ 29 ]. In their study, a set of three pre-identified gene regions was considered.…”
Section: Resultsmentioning
confidence: 83%
“…It appears that the peripheral tolerance has to be established before a metastatic cancerous growth takes place. In this regard, it is important to mention the report by Türbachova et al . on higher Treg cell ratio in peripheral blood tolerance and metastasis.…”
Section: The Possibilities To Circumvent Treg Cell‐based Constraintsmentioning
confidence: 93%
“…This allows for a significantly broader range of acceptable sample conditions collected by clinical sites. By simply freezing and shipping the collected whole blood or tissue samples without any other additional steps, it allows for routine monitoring of patients and immune-monitoring during clinical trials, multicenter studies and retrospective studies as well as the comparison of results across different studies [ 157 , 158 ]. A common application of this standardized, epigenetic-based, immune diagnostic technology is monitoring cell-mediated immunity during immune-modulatory clinical trials for cancer patients or inflammatory diseases.…”
Section: Reviewmentioning
confidence: 99%